Combined Inhibition of Tumor Necrosis Factor ? and Interleukin-17 As a Therapeutic Opportunity in Rheumatoid Arthritis: Development and Characterization of a Novel Bispecific Antibody - Fischer, Jens A. A.; Hueber, Axel; Wilson, Stacy; Galm, Margarete; Baum, Wolfgang; Kitson, Christopher; Auer, Johannes; Lorenz, Stefan H.; Moelleken, Joerg; Bader, Martin; Tissot, Alain C.; Tan, Seng-Lai; et al. (Arthritis and Rheumatology, 2015)
Rheumatoid arthritis therapies that are based on inhibition of a single cytokine, e.g., tumor necrosis factor ? (TNF?) or interleukin-6 (IL-6), produce clinically meaningful responses in only about half of the treated patients. This study was undertaken to investigate whether combined inhibition of TNF? and IL-17 has additive or synergistic effects in the suppression of mesenchymal cell activation in vitro and inflammation and tissue destruction in arthritis in vivo.Cultures of human fibroblast-like synoviocytes (FLS) were stimulated with TNF?, IL-17, or a combination of both. Single/combined neutralizing antibodies against TNF? and IL-17 were used to examine in vitro cytokine responses and in vivo development of arthritis and bone and cartilage destruction in TNF?-transgenic mice. Bispecific anti-TNF?/IL-17 antibodies were designed, and their potential to block cytokine responses in human FLS was tested.TNF? and IL-17 had additive/synergistic effects in promoting production of IL-6, IL-8, and granulocyte colony-stimulating factor, as well as matrix metalloproteinases, in FLS. Bispecific anti-TNF?/IL-17 antibodies showed superior efficacy in blocking cytokine and chemokine responses in vitro. Furthermore, dual versus single inhibition of both cytokines using neutralizing antibodies was more effective in inhibiting the development of inflammation and bone and cartilage destruction in arthritic mice.Combined blockade of TNF? and IL-17 was more effective than single blockade in inhibiting cytokine, chemokine, and matrix enzyme responses from human mesenchymal cells and in blocking tissue destruction associated with arthritis, and additionally showed a positive impact on rebalance of bone homeostasis. Bispecific anti-TNF?/IL-17 antibodies may have superior efficacy in the treatment of arthritis and may overcome the limited therapeutic responses obtained with single cytokine neutralization.
EVALuna2:13059